Practices in search of legitimacy: the contemporary use of ayahuasca, between religious and therapeutic vindications - David Dupuis (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2018)
In recent decades, the growing interest of Westerners in the psychotropic brew ayahuasca and the participation in exotic rituals has led to the multiplication of "shamanic centers" in the Peruvian Amazon. Among these, Takiwasi is a therapeutic community that welcomes hundreds of national and foreign clients every year. This institution, created by a French physician in 1992, was originally intended to propose a therapeutic alternative for the treatment of addiction, characterized by the use of tools of Peruvian mestizo shamanism, biomedicine and clinical psychology. The diachronic evolution of the institution is however marked by the growing use of elements of the Catholic tradition. In this article, I will examine the hypothesis that these transformations can be interpreted as the effects of the globalization of the use of ayahuasca and its legal and political consequences. Thus, the case of Takiwasi underlines the role played by religious traditions and the medical field in the construction, legitimization and maintenance of new and hybrid practices that are multiplying around the use of ayahuasca.